Exploring the relationship of static and dynamic balance with muscle mechanical properties of the lower limbs in healthy young adults - Hill, Mathew W.; Wdowski, Maximilian M.; Rosicka, Katarzyna; Kay, Anthony D.; Muehlbauer, Thomas (Frontiers in Physiology, 2023)
There is emerging evidence that mechanical properties of in vivo muscle tissues are associated with postural sway during quiet standing. However, it is unknown if the observed relationship between mechanical properties with static balance parameters generalise to dynamic balance. To determine the relationship between static and dynamic balance parameters with muscle mechanical properties of the ankle plantar flexors (lateral gastrocnemius [GL]) and knee extensors (vastus lateralis [VL]) in vivo. Twenty-six participants (men = 16, women = 10; age = 23.3 ± 4.4 years) were assessed for static balance (centre of pressure [COP] movements during quiet standing), dynamic balance (reach distances for the Y-balance test) and mechanical properties (stiffness and tone) of the GL and VL measured in the standing and lying position. Significant (p < .05) small to moderate inverse correlations were observed between the mean COP velocity during quiet standing with stiffness (r = -.40 to -.58, p = .002 to .042) and tone (r = -.42 to -.56, p = .003 to .036) of the GL and VL (lying and standing). Tone and stiffness explained 16–33% of the variance in the mean COP velocity. Stiffness and tone of the VL measured in the lying (supine) condition were also inversely significantly correlated with Y balance test performance (r = -.39 to -.46, p = .018 to .049). These findings highlight that individuals with low muscle stiffness and tone exhibit faster COP movements during quiet standing, indicative of reduced postural control but also reveal that low VL stiffness and tone are associated with greater reach distances in a lower extremity reaching task, indicative of greater neuromuscular performance.